Opportunities and challenges for the integration of managing non-communicable diseases within HIV care and treatment services in Tanzania - Anzibert Andrew Rugakingira; Emili Yondu; Joseph Matobo Thobias; Ikunda Dionis; Costantine Chasama Kamata; Manase Kilonzi; Emmy Metta; Nathanael Sirili (HIV Research & Clinical Practice)
Background People living with HIV and non-communicable diseases (NCDs) are reported to experience challenges in accessing affordable and high-quality NCD care services. Consequently, the World Health Organization (WHO) recommends care integration of NCDs within the HIV services in resource-limited regions. The available opportunities and challenges need to be understood and addressed for an effective integration process. This study explored opportunities and challenges for integrating NCDs within HIV care and treatment services in Tanzania. Methods An exploratory qualitative case study was conducted in Tanzania between April and July 2022. A total of 22 key informants working at the ministerial level, supervising the provision of healthcare services in Tanzania, were recruited purposefully for in-depth interviews. Thematic analysis was employed during the study. Results Several opportunities were identified in the study for HIV/NCD services integration including the existence of an integration policy, the availability of regulations and guidelines, the existence of donor support, the presence of physical space and reliable information and communication systems, human resources adequacy, and political will to support the process. However, participants voiced concerns over the costs related to service integration, difficulties in reallocating donor funds, and hesitance of the healthcare providers as likely challenges to effective integration. Conclusion The findings of this study underscore that the effective and sustainable care integration of NCDs within HIV services relies on the availability of policy, funds, infrastructures, human resources, and stakeholders’ willingness to support the process.